Satellite dish antenna control for distributed mobile telemedicine nodes - Bonaventure Onyeka Ekengwu; Paulinus Chinaenye Eze; Christopher Nnaemeka Asiegbu; Samuel Chukwuemeka Olisa; Chimezie Felix Udechukwu (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
The positioning control of a dish antenna mounted on distributed mobile telemedicine nodes (DMTNs) within Nigeria communicating via NigComSat-1R has been presented. It was desired to improve the transient and steady performance of satellite dish antenna and reduce the effect of delay during satellite communication. In order to overcome this, the equations describing the dynamics of the antenna positioning system were obtained and transformed into state space variable equations. A full-state feedback controller was developed with forward path gain and an observer. The proposed controller was introduced into the closed loop of the dish antenna positioning control system. The system was subjected to unit step forcing function in MATLAB/Simulink simulation environment considering three different cases so as to obtain time domain parameters that characterized the transient and steady-state response performances. The simulation results obtained revealed that the introduction of the full state feedback controller provided improved position tracking to unit step input with a rise time of 0.42 s, settling time of 1.22 s, and overshoot of 4.91%. With the addition of the observer, the rise time achieved was 0.39 s, settling time of 1.31 s, and overshoot of 10.7%. The time domain performance comparison of the proposed system with existing systems revealed its superiority over them.